Improving the Efficacy of Mesenchymal Stem/Stromal-Based Therapy for Treatment of Inflammatory Bowel Diseases - Mercedes Lopez-Santalla (MDPI AG, 2021)
Inflammatory bowel diseases (IBD) consisting of persistent and relapsing inflammatory processes of the intestinal mucosa are caused by genetic, environmental, and commensal microbiota factors. Despite recent advances in clinical treatments aiming to decrease inflammation, nearly 30% of patients treated with biologicals experienced drawbacks including loss of response, while others can develop severe side effects. Hence, novel effective treatments are highly needed. Mesenchymal stem/stromal cell (MSCs) therapy is an innovative therapeutic alternative currently under investigation for IBD. MSCs have the inherent capacity of modulating inflammatory immune responses as well as regenerating damaged tissues and are therefore a prime candidate to use as cell therapy in patients with IBD. At present, MSC-based therapy has been shown preclinically to modulate intestinal inflammation, whilst the safety of MSC-based therapy has been demonstrated in clinical trials. However, the successful results in preclinical studies have not been replicated in clinical trials. In this review, we will summarize the protocols used in preclinical and clinical trials and the novel approaches currently under investigation which aim to increase the beneficial effects of MSC-based therapy for IBD.